Physicochemical and adsorptive properties of biochar derived from municipal sludge: sulfamethoxazole adsorption and underlying mechanism - Qiu, Xiaojie; Zhao, Yingxin; Zhao, Cailian; Jin, Ruotong; Li, Chenxi; Mutabazi, Emmanuel (Frontiers in Environmental Science, 2023)
Municipal sludge waste could be transformed into useful biochar through pyrolysis process. In this study, municipal sludge-derived biochar (SBC) was successfully synthesized via the one-pot pyrolysis method, and the yield of sludge biochar gradually decreased with the pyrolysis temperature increased from 300°C to 800°C. The sludge biochar exhibited an alkaline surface due to the gradual accumulation of ash and the formation of carbonate and organic anion during high-temperature pyrolysis process. Moreover, the prepared samples were analyzed by different characterization techniques including BET, SEM, and XPS. Adsorption experiments using the optimized biochar sample of SBC800 resulted in a 95% sulfamethoxazole (SMX) removal efficiency and the maximum adsorption capacity of 7033.4 mg/kg, which was 47.5 times higher than that of SBC300. The adsorption process of SBC800 for SMX was more in line with the Freundlich and D-A isotherm model, the whole process was an exothermic reaction. SBC800 could effectively remove SMX through pore filling effect, electrostatic attraction, hydrogen bonding, hydrophobic effect, and π-π EDA interaction. Site energy distribution analysis showed that SMX preferentially occupied the high-energy adsorption site of SBC800, and then gradually diffused to the low-energy adsorption site. This study proposed a sustainable method for recycling municipal sludge for organic pollutant removal.